PENINGKATAN PEMAHAMAN MAHASISWA PADA MATA KULIAH TELAAH KURIKULUM MELALUI MEDIA VISUAL BERBASIS MACROMEDIA FLASH MX - Hadi, Syamsu (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
The objective of the research was to know the effectiveness of visual media based on macromedia flash MX in teaching Curriculum Study to improve students understanding. It was a class action research at Office Administration Education class consisted of 50 students. The result of the study showed that visual media based on macromedia flash MX was effective to improve studentsâ understanding on Curriculum Study. Moreover, it also improved studentsâ activeness and attention during the teaching learning process. Thus; it suggested for: (1) the institution to prepare all facilities and amenities such as LCD, computer, internet network, etc since the implementation of this media need those facilities, (2) the lecturers to master how to use the media and prepare their own materials so they can teach well.